Guanidine-resistant poliovirus mutants produce modified 37-kilodalton proteins. - Anderson-Sillman, K (1984)
Eighteen spontaneous, guanidine-resistant mutants of poliovirus were obtained by plaque selection. Isoelectric focusing demonstrated charge changes in a 37-kilodalton protein, pX, among three of the mutants. The precursor of pX, NCVP5b , also exhibited charge changes among the three mutants. pX of 12 mutants was also examined by peptide mapping with Staphylococcus aureus V8 protease. Nine of the mutants presented modified maps, and seven of these maps were identical. The demonstration of mutational changes in pX in 12 of 18 mutants suggests a role for this protein in determining the guanidine trait of poliovirus and corroborates studies with foot-and-mouth disease virus.